Opportunities Of Digital Pedagogy in A Modern Educational Environment (Journal of Pedagogical Inventions and Practices, 2021)
The article lists the role and importance of digital pedagogy in ensuring the quality of higher education. The factors that have a positive effect on the quality and effectiveness of education are analyzed. The analysis of the features of using traditional and digital pedagogy in the educational process is described.